Illuminating the signalomics of microbial biofilm on plant surfaces. (January 2023) - Patwardhan, Sanchita Bipin; Pandit, Chetan; Pandit, Soumya; Verma, Devvret; Lahiri, Dibyajit; Nag, Monupriya; Ray, Rina Rani; Jha, Priyanka; Prasad, Ram
Abstract: A vast variety of microorganisms are supported by plants both aboveground and belowground and such close association may be beneficial in terms of the growth and productivity of the plant. These microbes residing within the biofilm matrix formed on plant surfaces possess unique characteristics. The biofilm bound microbes produce different signals regulated by several physical, biological, and genetic factors. These signals accentuate the plant-microbe chemistry and are predominantly involved in improving the lifestyle of both partners by helping them to thrive under environmental stress. The potential of the plant to endure stress, defend the enemy and acquire resistance through chemical communication is effectively utilized for agricultural betterment with plant growth-promoting rhizobacteria (PGPR). Although the significance of this signalomics and the consequent inter-kingdom co-evolution, are not fully explored, research is going on to analyse these signals and other factors that influence the microbial biofilm formation on plant surfaces with some targeted objectives. Graphical abstract: Image 1 Highlights: Mechanism and internal factors affecting the biofilm formation on plant surface is briefly explained. Several mechanisms of chemical signalling between the plant surface and the bacterial biofilm are described in details. Different types of association between the bacterial biofilm and plants are elaborated. Effect of signalling from plant metabolites on biofilm formation is highlighted. Industrial application of bacterial biofilm association with plant surface is described.